Planning and Management of Patient Flow and Bed Capacities of Cardiac Ward with Mathematical Modeling and Discrete Event Simulation Approach - mohsen afsahi; Mohammad Mehdi Sepehri; ehsan ameri (بیمارستان, 2015)
Background: Deciding on the number of hospital beds is one of the most serious challenges managers face. More hospital beds result in higher running cost although less hospital beds might cause disorder in patients flow.  Minimizing total cost besides maximizing the patients flow in a hospital network, considering the practical limitations is the main objective of this survey.